Analysis of the Internal Control System of Cash Receipts and Disbursements - Destalia Puteri, Ajeng; Indrawan, Andri; Martaseli, Evi (Universitas Muhammadiyah Metro, 2024)
This study aims to analyze the extent to which the internal control system of cash receipts and disbursements is implemented at PT. Sinar Sosro Sukabumi Sales Office in carrying out its business activities in order to achieve company goals. The theory used in this study is the theory according to Mulyadi. The research method used in this study is a qualitative research method, with descriptive data analysis techniques, namely data obtained from interviews and observations as well as documentation. Where the data taken is secondary and primary data in the form of evidence of records or historical reports of the company. The results of this study indicate that the internal control system of cash receipts and disbursements applied at PT. Sinar Sosro KP. Sukabumi is not completely good yet, because there are still elements that are not in accordance with Mulyadi's theory. of which there are still multiple functions where the cash function performed by the cashier turns out to be in charge of the accounting department as well. Cash and related parts of cash have not been insured by the company. It is feared that this will reduce the accuracy of the records and will open up opportunities for employees to commit cash fraud which can be detrimental to the company. This will also reduce the effectiveness of the cashier's work practices, because it holds two functions simultaneously